ANALISIS EKONOMI TEBANG PILIH TANAM INDONESIA (TPTI) DAN TEBANG JALUR TANAM INDONESIA (TJTI) DALAM PEMBANGUNAN KEHUTANAN DI LUAR JAWA - B D Nasendi (Jurnal Penelitian Hasil Hutan, 1996)
Demand side economic analysis  or the so called market approach economic analysis was conducted  to evaluate  the Indonesian Selective  Cutting and Planting  System  (IPTI)  and its complementary  technique called  TJTI (Indonesian Strip  Cutting  and Planting System) at PT. ITCI (International  Timber Corporation Indonesia) Forest Concession Management and Operations in East Kalimantan.The analysis proved that the logs produced and marketed both with TPTI and TJTI systems of forestry  operations  and practices  in East Kalimantan,  one of the Indonesian Outer Java Inslands rich tropical forest archipelagoes is viable and economically feasible to maintain  the sustainable production  and  marketing.  However, further research is needed to evaluate the resource and supply side economic analysis including sustainable forest  resource management, minimum and maximum management unit sizes of both TJTI and TPTI and its sustainability  in terms of production,  socio-economic  and ecological-biophysical.Key words:   Economic  analysis,   TPTI,   TJTI and  Sustainable Forest Management.